Aplikasi Pemberian Kredit Pada PT. BPR Gerbang Serasan Dengan Model Credit Scoring - Ansesha Yorika; Solikin, Imam; Sopiah, Nyimas; Oktarina, Tri (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
BPR Gerbang Serasan Kabupaten Muara Enim is a financial institution whose main activity is collecting funds from the community in the form of savings and deposits and channeling them back to the community in the form of credit. In granting credit, BPR must manage and analyze it as best as possible by paying attention to elements of credit worthiness. However, until now the credit granting process tends to be manual and takes quite a long time to produce supporting documents for the credit committee because it still uses simple methods, namely handwriting and data processing that relies on Microsoft Excel, so this is deemed necessary. lack. effective and efficient because it is prone to errors and data redundancy. Therefore, a responsive web-based application is needed to facilitate the entire credit granting process. The credit scoring model is used to assess potential debtors based on financial and non-financial information. In this research, the application of the credit scoring model in the form of a web application makes it possible to provide accurate credit decisions. In addition, developing a simple system using the waterfall method allows for departmentalization and control, thereby minimizing the possibility of errors. The results of this research are expected to provide a significant contribution to PT. BPR Gerbang Serasan Kabupaten Muara Enim in increasing the efficiency of the credit granting process which is useful in the form of reports and supporting documents for the credit committee.